2012
DOI: 10.1177/0883073811435507
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peroxisomal Biogenesis Factor 7 and Autism Spectrum Disorders in a Korean Population

Abstract: Autism spectrum disorder is a neurodevelopmental disorder characterized by deficits in social communication, impaired reciprocal social interaction, and repetitive patterns of behaviors or interests. Although the cause of autism spectrum disorder remains elusive, the present study identified peroxisomal biogenesis factor 7 (PEX7) as a gene associated with autism spectrum disorder, and this association was examined in a Korean population. PEX7 encodes a cytosolic receptor for peroxisome targeting signal 2 of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The consortium behind that study identified a mutation affecting the WD‐40 domain of PEX7 in three affected children, but not in the nonaffected siblings, of consanguineous parents. This discovery supports the findings in an earlier paper, which proposed an association between single nucleotide polymorphisms in PEX7 and autism . Furthermore, retrospective screening of the clinical records of previously reported RCDP patients revealed that two patients with less severe disease course had later been diagnosed with a neurodevelopmental condition (autism and attention deficit hyperactivity disorder) .…”
Section: Potential Involvement Of Ether Lipids In More Common Neurolosupporting
confidence: 89%
“…The consortium behind that study identified a mutation affecting the WD‐40 domain of PEX7 in three affected children, but not in the nonaffected siblings, of consanguineous parents. This discovery supports the findings in an earlier paper, which proposed an association between single nucleotide polymorphisms in PEX7 and autism . Furthermore, retrospective screening of the clinical records of previously reported RCDP patients revealed that two patients with less severe disease course had later been diagnosed with a neurodevelopmental condition (autism and attention deficit hyperactivity disorder) .…”
Section: Potential Involvement Of Ether Lipids In More Common Neurolosupporting
confidence: 89%
“…In 2013, a study applying whole exome sequencing identified a link between mutations in PEX7 (RCDP type 1) and autism spectrum disorder, a range of neurodevelopmental conditions characterized by deficits in communication and social interaction and repetitive behavior, in a family with three affected children [256]. This observation supports previous work showing an association between single nucleotide polymorphisms in the PEX7 gene and autism [257]. Prompted by their findings, the authors reviewed previously reported RCDP cases for potential signs of autism and found two further patients, which had later been diagnosed with neurodevelopmental conditions (one with autism, the other with attention deficit hyperactivity disorder) [256].…”
Section: The Contribution Of Peroxisomes To More Common Neurological supporting
confidence: 57%
“…This hypothesis is now supported by various observations, including the identification of reduced plasmalogen levels in the blood of autistic patients [34], and reports about clinical diagnoses of ASD and ADHD in patients with RCDP [17,35]. The genetic link between PEX7 and ASD, as proposed in two recent publications [17,36], further adds to these findings. Even more, de novo mutations in another ether lipid-metabolizing enzyme, alkylglycerol monooxygenase, have been identified in autistic patients by two independent studies [37,38].…”
Section: Discussionmentioning
confidence: 62%